Quantitative trait locus mapping in mice identifies phospholipase Pla2g12a as novel atherosclerosis modifier. (October 2017) - Nicolaou, Alexandros; Northoff, Bernd H.; Sass, Kristina; Ernst, Jana; Kohlmaier, Alexander; Krohn, Knut; Wolfrum, Christian; Teupser, Daniel; Holdt, Lesca M.
Abstract: Background and aims: In a previous work, a female-specific atherosclerosis risk locus on chromosome (Chr) 3 was identified in an intercross of atherosclerosis-resistant FVB and atherosclerosis-susceptible C57BL/6 (B6) mice on the LDL-receptor deficient ( Ldlr −/− ) background. It was the aim of the current study to identify causative genes at this locus. Methods: We established a congenic mouse model, where FVB.Chr3 B6/B6 mice carried an 80 Mb interval of distal Chr3 on an otherwise FVB. Ldlr −/− background, to validate the Chr3 locus. Candidate genes were identified using genome-wide expression analyses. Differentially expressed genes were validated using quantitative PCRs in F0 and F2 mice and their functions were investigated in pathophysiologically relevant cells. Results: Fine-mapping of the Chr3 locus revealed two overlapping, yet independent subloci for female atherosclerosis susceptibility: when transmitted by grandfathers to granddaughters, the B6 risk allele increased atherosclerosis and downregulated the expression of the secreted phospholipase Pla2g12a (2.6 and 2.2 fold, respectively); when inherited by grandmothers, the B6 risk allele induced vascular cell adhesion molecule 1 ( Vcam1 ). Down-regulation of Pla2g12a and up-regulation of Vcam1 were validated in female FVB.Chr3 B6/B6 congenic mice, which developed 2.5 greater atherosclerotic lesions compared to littermate controls ( p =0.039). Pla2g12a was highly expressed in aortic endothelial cells in vivo, and knocking-down Pla2g12a expression by RNAi in cultured vascular endothelial cells or macrophages increased their adhesion to ECs in vitro . Conclusions: Our data establish Pla2g12a as an atheroprotective candidate gene in mice, where high expression levels in ECs and macrophages may limit the recruitment and accumulation of these cells in nascent atherosclerotic lesions. Highlights: QTL mapping revealed a female-specific atherosclerosis risk locus on mouse Chr3. Locus fine-mapping identified Vcam1 and Pla2g12a as parallel risk-determining factors. Pla2g12a is a novel atherosclerosis modifier. Transcriptional downregulation of the secreted phospholipase Pla2g12a confers risk. Pla2g12a is atheroprotective by limiting adhesion of macrophages to the endothelium.